Pengaruh Budaya Berwirausaha Dan Pendidikan Kewirausahaan Terhadap Minat Berwirausaha Mahasiswa Di Universitas Bhakti Husada Indonesia - Hendra Rustama (Entrepreneur: Jurnal Bisnis Manajemen dan Kewirausahaan, 2026)
This study aims to determine the influence of entrepreneurial culture on students' entrepreneurial interest and to find out the influence of entrepreneurship education on students' entrepreneurial interest. This method uses a quantitative research method with an associative study. The research location is at Bhakti Husada Indonesia University with the population and sample being students. The research instrument uses a questionnaire. The operational definitions of the variables used in this study are Entrepreneurial Interest (Y), Entrepreneurial Culture (X1), and Entrepreneurship Education (X2). The data analysis technique uses descriptive statistics and classical assumptions, with hypothesis testing processed using SPSS. The research results show that the influence of Entrepreneurial Culture and Entrepreneurship Education on Entrepreneurial Interest F-count 153.773 > F-table 3.090 (sig 0.000), with sig 0.000 < 0.05 indicating that H0 is rejected and Ha is accepted.